Convergence and university media: An approach to the new ecuadorian scenario (2018)
The Ecuadorian media are immersed in processes of structural changes generated by a constant such as technological advances, but also by the entry into force of regulations such as the Organic Law of Communication. The university media, although with a minor presence and with marked differences compared to the conventional means, do not escape these modifications, having even to consider the aspects related to the Ecuadorian higher education, which lives its own time of transformations. This article of reflection seeks to deepen in these aspects, with the purpose of clarifying the scenario to reflect on the convergence in the university media. © 2018, Universidad del Zulia. All rights reserved.